Publish and perish: A new look at bibliometric statistics in the PBRF age - Chambers, Geoffrey; Gardner, Jonathan; Smith, Alastair (New Zealand Science Review, 2010)
​There is no doubt that New Zealand scientists are living uncomfortably in a new age of accountability – the so-called ‘audit society’ (Power 1997). It is scant comfort to know that we are not alone in the world either (Lawrence 2007). This article is concerned with finding the best and most ethical way for scholars and scientists to present reliable evidence concerning the quantity and quality of their published research output and how this may influence their decisions about where to submit their manuscripts.